Research methods and methodologies in education - Coe, Rob; Waring, Mike; Hedges, Larry V.; Arthur, James, 1957- (London : SAGE Publications Ltd, 2017)
Using a variety of methodological approaches and research techniques in education, this book sets out to provide students with the theoretical understandings, practical knowledge and skills which they need to carry out independent research.
Chapter 1: Introduction -- Robert J. Coe PART I: INTRODUCTION TO RESEARCH METHODS AND METHODOLOGIES IN EDUCATION Chapter 2: The nature of educational research -- Robert J. Coe Chapter 3: Finding your theoretical position -- Michael Waring PART II: BASIC PRINCIPLES AND PRACTICE IN CONDUCTING RESEARCH Chapter 4: Design of empirical research -- Larry V. Hedges Chapter 5: Planning your research -- Laura Day Ashley Chapter 6: Inference and interpretation in research -- Robert J. Coe Chapter 7: Research ethics -- Martyn Hammersley PART III: RESEARCH DESIGNS Chapter 8: Action research -- Carol Munn-Giddings Chapter 9: Naturalistic research -- Rob Walker Chapter 10: Ethnographic research -- Ghazala Bhatti Chapter 11: Visual methodologies -- Claudia Mitchell Chapter 12: Grounded theory -- Michael Waring Chapter 13: Case study research -- Laura Day Ashley Chapter 14: Secondary data -- Emma Smith Chapter 15: Longitudinal research -- Anna Vignoles Chapter 16: Statistical and correlational techniques -- Stephen Gorard Chapter 17: Impact evaluation -- Steve Higgins Chapter 18: Interventions: experiments -- Peter Tymms Chapter 19: Mixing methods in education research -- Gert Biesta Chapter 20: Systematic reviews -- Carole Torgerson, Jill Hall, Kate Lewis-Light PART IV: DATA COLLECTION TOOLS Chapter 21: In-depth interviews -- Carolyn L. Mears Chapter 22: Focus groups and group interviews -- Anita Gibbs Chapter 23: Internet-based methods -- Rhona Sharpe and Greg Benfield Chapter 24: Doing social media research -- Eve Stirling Chapter 25: Documentary methods -- Gary McCulloch Chapter 26: Questionnaires -- Peter Tymms Chapter 27: Measurement and validity -- Ronald K. Hambleton PART V: ANALYSIS METHODS Chapter 28: Using software in qualitative data analysis -- Graham R. Gibbs Chapter 29: Statistical analysis tools -- Paul Connolly Chapter 30: Discourse analysis -- Elaine Vaughan Chapter 31: Media analysis -- Michael Atkinson Chapter 32: Biographical research -- Michael Tedder Chapter 33: Statistical hypothesis tests -- Michael Borenstein Chapter 34: Analysis of variance (ANOVA) -- H. J. Keselman and Lisa Lix Chapter 35: Multiple linear regression -- Stephen Gorard Chapter 36: Multilevel analysis -- Michael Seltzer and Jordan Rickles Chapter 37: Effect size -- Robert J. Coe Chapter 38: Meta-analysis -- Larry V. Hedges.
Previous edition : edited by James Arthur [and others] 2012.
Includes bibliographical references and index.
Keywords: Education -- Research -- Methodology; Education -- Research